1977
DOI: 10.1055/s-0028-1097530
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Longibornane Sesquiterpenes

Abstract: Essentially complete analyses are reported of the sesquiterpene fractions from the leaf oils of Pinus l o n g i f o l i a , P. pinaster, P. t h u n b e r g i i , P. d e n s iflora, C h a m a e c y p a r i s n o o t k a t e n s i s and C. o b t u s a and of oil from the liverwort S cap a n ia u n d u 1 a t a. These species have been recorded as sources of longi/olene and related compounds but the present results differ considerably from those of the previous (often incomplete) analyses. The best sources of long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Some studies have reported that compound as responsible for larvicidal activity against Anisakis simplex (Navarro et al, 2008) and acaricidal activity on Rhipicephalus (Boophilus) microplus (Chagas et al, 2002). The quantity found of longifolene (32.95%) was interesting, indicating that M. quinquenervia as a good source of this substance, since according to Banthorpe et al (1977), the best sources of longifolene and its related compounds are Pinus pinaster and Silene undulata (16% and 46% of the steam volatile oil, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have reported that compound as responsible for larvicidal activity against Anisakis simplex (Navarro et al, 2008) and acaricidal activity on Rhipicephalus (Boophilus) microplus (Chagas et al, 2002). The quantity found of longifolene (32.95%) was interesting, indicating that M. quinquenervia as a good source of this substance, since according to Banthorpe et al (1977), the best sources of longifolene and its related compounds are Pinus pinaster and Silene undulata (16% and 46% of the steam volatile oil, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…In spite or the great commercial importance of turpentine oil as starting material for pharmaceuticals [1] and synthetic fragrances [2], the knowledge of its minor constituents is limited. Only 12 components have so far been identified [3], although detailed analysis of the maritime pine leaf oil have been reported [4,5,6].…”
mentioning
confidence: 99%